Mothers and Children Right and Need for Essential Services Accessibility in Communities - Panngam, Nittaya; Nuntaboot, Khanitta (Talenta Publisher, 2020)
Community play important role to enhance the accessibility to essential rights and services of mothers and children in community. This study utilizes the rapid ethnographic community assessment process (RECAP) to explore community potential for managing accessibility to rights and services of mothers and children in communities. The study was conducted in 8 sub-districts of 8 provinces in 4 regions nationwide. There are 146 informants recruited from purposive sampling include family members, community leaders, local leaders, health care providers, and social groups. Data were collected by the participated observation, in-depth interview, focus group discussion, as well as consultation using interview and focus group guidelines. Data were analyzed using content analysis and thematic analysis. The results reveal two parts include 1) sociocultural context of mothers and children which demonstrate need and way of life of pregnant women and child rearing; and 2) community managing to enhance essential right and service accessibility of mothers and children includes (1) managing fundamental right and services; (2) health services; (3) social welfare and community funds; (4) development safe and learning-enhanced environment; (5) educational services; (6) managing sources of information; and (7) caring based on cultural and traditional way. Based on this findings, national policy makers and relevant stakeholders could be utilizing for improvement prospective development and national policy to reinforce and strengthen community organizations contributing to health development of mothers and children. Â Keywords: Rapid Ethnographic Community Assessment Process, Maternal Rights, Child Rights, Services for Mother and Child, Service Accessibility, Community Management